Impact of monetary and fiscal policy to Bursa Malaysia Plantation Index / Yaqin Yunus and Amalina Ismail - Yunus, Yaqin; Ismail, Amalina (Faculty of Plantation and Agrotechnology, 2018)
Play a role to regulate monetary flow while fiscal policy imposed by Malaysian Government play a role to manage public monetary. Progressive growth and development of country economy can be achieved through effective monetary and fiscal policy. Plantation is one of important industry in Malaysia that contribute to the country economy and social interest. In 2016r agriculture sector stood at 8.1 per cent or RM89.5 billion to the Gross Domestic Product (GDP). The purpose of this study is to determine the relationship of monetary and fiscal policy with plantation economy in Malaysia. Overnight Policy Rate (OPR) is used as monetary policy instrument and fiscal expenditure and government revenue are used as fiscal policy instruments while Bursa Malaysia Plantation Index is used as plantation sector economic performance. This study used 30 samples of secondary data from 1st quarter 2011 until 2nd quarter of 2018. The research is examined with unit root test, cointegration test. VECM Model and Granger Causality Test and diagnostic test using quarter data from year 2011 until 2018. The results revealed that fiscal expenditure and government revenue have significant impact to Bursa Malaysia Plantation Index in long run while Overnight Policy Rate (OPR) has significant impact to Bursa Malaysia Index in short run. Thus, monetary policy and fiscal policy should also be considered among all factors that impact the plantation economy. Policy makers, investors and corporations may utilize these findings for their strategic decision.